1978
DOI: 10.1007/bf00777522
|View full text |Cite
|
Sign up to set email alerts
|

Separation of nucleosomes containing histones H1 and H5

Abstract: Hen erythrocyte chromatin was digested with staphylococcal nuclease and fractionated by electrophoresis in polyacrylamide gels. Instead of the three bands described for mouse carcinoma chromatin, four main discrete components (MN1, MN2, MN2E and MN3) were resolved in the mononucleosome fraction of erythrocyte chromatin. MN2 contained all five histones and a DNA fragment of 165--180 base pairs. MN2E comprised four nucleosomal histones plus histone H5 (but not H1) and a DNA fragment of 170--190 base pairs. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1980
1980
1985
1985

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…We find two erythrocyte chromatosomes in addition to the core nucleosome, as has been reported (32). Unlike yeast, the erythrocyte core particle accumulates continuousiv relative to larger soluble nucleoproteins during the course of digestion ( Figure 4B).…”
Section: Mononucleosomes Electrophoretic Patterns Of Soluble Nucleopsupporting
confidence: 82%
“…We find two erythrocyte chromatosomes in addition to the core nucleosome, as has been reported (32). Unlike yeast, the erythrocyte core particle accumulates continuousiv relative to larger soluble nucleoproteins during the course of digestion ( Figure 4B).…”
Section: Mononucleosomes Electrophoretic Patterns Of Soluble Nucleopsupporting
confidence: 82%
“…Upon further digestion a third nucleosome appeared (MN3), the yields of subnucleosomes SN7, SN4, and SN1 were enhanced, and other subnucleosomes virtually disappeared. Second-dimension electrophoresis confirmed that MN2, MN1, and MNC were nucleosomes containing HI (MN2), nucleosomes containing H5 (MN1), and nucleosome cores (MNC), as described by Bakayeva & Bakayev (1978). MN3 contained core histones, HI, and a few nonhistone proteins, mainly one that remained near the top of 15% gels containing NaDodS04 (not shown).…”
Section: Resultsmentioning
confidence: 52%
“…The difference in mobilities of MN2 and MN20 particles in DNP gels is of interest. This is analogous to H5-containing mononucleosomes ("MN2E") moving 22 faster than HI-containing MN2 particles in DNP gels . This could have arisen by MN2E being more negatively charged, because its DNA was 5 to 10 base pairs longer than that in MN2 , although Simpson apparently found no difference in DNA lengths between such particles.…”
Section: Discussionmentioning
confidence: 85%